Spatial Analysis of The Influence of Education And Income on Indonesia's Democracy Index In 2015 And 2019 - Abiduloh, Fauzan Zahid; Hasan, Chotib (HK-Publishing, 2021)
Abstract:This research discusses the spatial effects of education and income influences on the 2015 and 2019 Democracy Index of Indonesia. The income variable used is Gross Regional Domestic Product (GRDP) per capita, and the education variable used is the average year of schooling. All of the data are collected from the website of the Indonesian Central Bureau of Statistics, namely www.bps.go.id. Using spatial econometrics, researchers found that the distribution of the democratic index value in each province forms a group spatial systemic pattern. Provinces with high democracy index scores tend to be surrounded by provinces that have high democracy index scores, while provinces with low democracy index scores tend to be surrounded by provinces that have low democracy index scores. Researchers also found a spatial dependence on the influence of education and income on the index of democracy in neighboring provinces. Thus, it can be concluded that the quality of democracy in a province is not only caused by the level of education and income in the province, but also by its neighboring provinces.Keywords: indonesiaâ€™s democracy index, education, income, spatial econometrics.Â Abstrak:Penelitian ini membahas pengaruh spasial variabel pendidikan dan pendapatan terhadap Indeks Demokrasi Indonesia 2015 dan 2019. Variabel pendapatan yang digunakan adalah Produk Domestik Regional Bruto (PDRB) perkapita, dan variabel pendidikan yang digunakan adalah rata-rata lama sekolah. Semua data dikumpulkan dari website Badan Pusat Statistik Indonesia, yaitu www.bps.go.id. Dengan menggunakan ekonometrik spasial, peneliti menemukan bahwa sebaran nilai indeks demokrasi di setiap provinsi membentuk pola sistemik spasial berkelompok. Provinsi dengan skor indeks demokrasi yang tinggi cenderung dikelilingi oleh provinsi yang memiliki skor indeks demokrasi yang tinggi pula, sedangkan provinsi dengan skor indeks demokrasi yang rendah cenderung dikelilingi oleh provinsi yang memiliki skor indeks demokrasi rendah. Peneliti juga menemukan adanya efek spasial dalam pengaruh pendidikan dan pendapatan terhadap indeks demokrasi di provinsi tetangga. Dengan demikian, dapat disimpulkan bahwa kualitas demokrasi di suatu provinsi tidak hanya disebabkan oleh tingkat pendidikan dan pendapatan di provinsi tersebut, tetapi juga oleh provinsi tetangganya.Kata kunci: Â indeks demokrasi indonesia, pendidikan, pendapatan, ekonometrika spasial